The Aura-OMI Aerosol Index distribution over Greece - Kaskaoutis, D. G.; Nastos, P. T.; Kosmopoulos, P. G.; Kambezidis, H. D.; Kharol, S. K.; Badarinath, K. V. S. (Atmospheric Research, 2010)
The Aerosol Index (AI) observations derived from the Ozone Monitoring Instrument (OMI) on board the Dutch-Finnish Aura satellite are analyzed over Greece covering the period from September 2004 to August 2008. The AI data cover the whole Greek territory (34°-42°N, 20°-28°E) with a spatial resolution of 0.25° × 0.25° The results show significant spatial and temporal variabilities of the seasonal and monthly-mean AI, with higher values at the southern parts and lower values over northern Greece. On the other hand, the AI values do not show significant differences between the western and eastern parts and, therefore, the longitude-averaged AI values can be utilized to reveal the strong south-to-north gradient. This gradient significantly changes from season to season being more intense in spring and summer, while it is minimized in winter. Another significant remark is the dominance of negative AI values over northern Greece in the summer months, indicating the presence of non-UV-absorbing aerosols, such as sulfate and sea-salt particles. The great geographical extent of the negative AI values in the summer months is indicative of long-range transport of such aerosols. In contrast, the high positive AI values over southern Greece, mainly in spring, clearly reveal the UV-absorbing nature of desert-dust particles affecting the area during Saharan dust events. The annual variation of spatial-averaged AI values shows a predominant spring maximum (0.424 ± 0.329, in April) due to dust particles, which dominate this average and a summer minimum due to the negative AI values observed over northern Greece. In the cold period of the year (November to February) the AI values are higher over northern Greece compared to those in south, while in the rest of the year the opposite is true. © 2010 Elsevier B.V.
Keywords: Absorbing aerosol; Absorbing aerosols; aerosol; Aerosol Index; Atmospheric aerosols; dust; Greece; long range transport; OMI; Ozone; particle size; Satellite imagery; Size distribution; Spatial distribution; spatial variation; temporal variation; Ultraviolet spectrometers